2014
DOI: 10.12738/estp.2014.6.2307
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of Gender Differences in terms of Teacher Views on the Instructional Leadership Behavior of Principals

Abstract: The main aim of this study was to gather teachers' views to determine the effect size of gender differences on the instructional leadership behavior of school principals. The standardized mean difference (SMD) was calculated to measure the effect size in this study. An initial search yielded 126 studies on the research topic, which consists of master theses, doctoral theses, and conference proceedings. After a detailed inclusion process, 38 studies, having data according to coding protocol, were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Instructional leadership roles of administrators are the basic requirement for school success (Hallinger, 2005). What distinguishes educational leadership from all other leadership approaches is its being unique to educational institutions (Kış & Konan, 2014). It focuses on educational leadership, which is the attitude of the school administrator to achieve the goals of the student and what needs to be done with them by affecting other stakeholders, practices such as explaining the school's goal, managing the teaching system and education, creating a positive school atmosphere, and tasks related to these issues (Buluç, 2009).…”
Section: Results Discussion and Recommendationsmentioning
confidence: 99%
“…Instructional leadership roles of administrators are the basic requirement for school success (Hallinger, 2005). What distinguishes educational leadership from all other leadership approaches is its being unique to educational institutions (Kış & Konan, 2014). It focuses on educational leadership, which is the attitude of the school administrator to achieve the goals of the student and what needs to be done with them by affecting other stakeholders, practices such as explaining the school's goal, managing the teaching system and education, creating a positive school atmosphere, and tasks related to these issues (Buluç, 2009).…”
Section: Results Discussion and Recommendationsmentioning
confidence: 99%
“…Various definition of instructional leadership has been stated by many researchers and scholars in educational leadership. One of them is a type of leadership that affect school's development (Kis & Konan, 2014) and a leadership that uses knowledge in solving academic problems and educating teachers to know their roles to realize the school goal (Krug, 1992). Drake and Roe (2002) defines instructional leadership as any effort towards encouraging and supporting parties that are involved in the T&L process to achieve school goal and developing a strong school social system.…”
Section: Definition Of Instructional Leadershipmentioning
confidence: 99%
“…Several previous studies have analyzed how the gender of the follower influences the ratings of leadership given to leaders. Kis and Konan (2014) conducted a meta-analysis of 38 studies with a total sample of 15,280 teachers and found that male teachers rated their principals' instructional behaviors higher than female teachers (d = .04). Paustina-Underdahl, Slattery, and Woeht (2014) conducted a meta-analysis for leader effectiveness.…”
Section: Cross-gender Leadership Studiesmentioning
confidence: 99%